Potret Sistem Agribisnis Pengolahan Hasil Perikanan Di Pesisir Pantai Selatan Kabupaten Garut - Wiryati, Ganjar (Jurnal Penyuluhan, 2019)
The purpose of this study was to determine the types of processed fisheries produced in the southern coast of Garut Regency and find out the fishery processing agribusiness system on the southern coast of Garut Regency. The method used in the study is descriptive method with qualitative and quantitative approaches. Sampling by purposive sampling. Sampling was conducted on 30 fish processing business people in six subdistricts (Pameungpeuk, Mekarsari, Cikelet, Caringin, Pakenjeng, Cibalong). Data collection techniques by means of interviews using questionnaire instruments containing a list of questions. In data processing, the determination of values (scores) for each question in each subsystem (subsystem of procurement and distribution of fisheries production facilities, production business subsystems, post production subsystems,marketing subsystems, supporting service subsystems). Research results obtained information on the types of processed that are produced include, salted fish, pindang fish, shredded fish, fish meatballs, crackers, nuget, agar-agar. Next in the review of the five business subsystems obtained values (Scores) Subsystems for procurement and distribution of facilities (7.7), production business subsystems, (10.2), post-production systems (7), marketing subsystems (9.3), sub supporting service system (9.6) from the results of the assessment obtained a portrait of fishery processing agribusiness in the South Coast of Garut Regency. The results of this study can be used as a reference to develop processing activities of fishery results on the southern coast of Garut Regency.